Ocular Surface Microbial Flora and Photorefractive Keratectomy - Alireza Peyman; Mehdi Bazukar; Tahmineh Narimani; Majid Mirmohammadkhani; Mohsen Pourazizi (Journal of Ophthalmology)
Purpose. To assess the influence of photorefractive keratectomy (PRK) on ocular surface microbial flora. Methods. A prospective study was conducted on patients who underwent PRK. The samples were taken from the inferior conjunctival fornix using a sterile swab, immediately before surgery, and then within three months following the PRK. The samples were tested using three culture mediums including blood agar, chocolate agar, and eosin methylene blue agar. Results. Thirty-five eyes of 35 patients including 19 females (54.3%) with a mean age of 24 ± 3.2 years were enrolled. The culture-positive rate was 15/35 eyes (42.9%) preoperative and 17/35 (48.6%) postoperative samples (P=0.47). The most common microorganisms isolated from preoperative samples were coagulase-negative Staphylococcus (CoNS) spp. in 14 (40%) samples, followed by Streptococcus spp. in 2 (5.7%), and Staphylococcus aureus in one (2.9%). Postoperative microorganisms isolated from conjunctival samples were CoNS spp. in 15 (42.9%), Streptococcus spp. in 3 (8.6%), and Staphylococcus aureus in one (2.9%), and Corynebacterium spp. in one (2.9%). Conclusion. This study indicated that there is not any remarkable difference in microorganisms isolated from conjunctival samples three months after PRK.